Abdominal Strap and Perineum Care after Delivery in Beninese Traditions - ALAGNIDE, Etienne; GANDEMA, S.; NIAMA NATTA, AKPOVI; DJIVOH, Yolande; Bankole, Viridiane; KPADONOU GODONOU, TOUSSAINT (My University, 2020)
Background: Several traditional methods are used for the preventive or curative management of the anatomical and physiological alterations which can occur with women after delivery, especially on abdominal strap and the perineum. Objective: To study methods used in the departments of Oueme and Plateau in Benin. Method: Prospective transversal study, descriptive and analytical. It consisted to interview, from February to July 2016, women who gave birth at least once and since at least three months, living in the departments of Oueme and Plateau in Benin and who consented to participate to the study. Dependent variables collected were the use or not of traditional methods for the management of abdominal strap and perineal alterations after delivery. Results: Women of the study were 32.83 ± 8.99 years old, as average. Their number of pregnancy was 5.42 ± 2.16, on average. Traditional methods were used 99.6% and 99.1% respectively for perineum and abdominal strap. It was mainly abdominal massage and intimate hygiene with a traditional soap. Methods used were started the day after delivery and for 6 weeks on average. Instrumentation use for delivery was the factor significantly associated with the use of these methods. The mode of delivery was therefore associated with the use of abdominal strap methods (p=0.00). Conclusion: After delivery, taking care of perineum and abdominal strap is very important for Beninese women. But it will be necessary to consider consequences of these methods, to ensure that their use is profitable for them at best.
Keywords: Delivery; Abdominal strap; Perineum; Traditional methods; Benin